Influence of Demographic Characteristics of Knowledge Management Enablers in Nepalese Hospitality Industry (Nepalese Journal of Hospitality and Tourism Management, 2022)
This paper examines the influence of demographic characteristics on knowledge management enablers in the hospitality industry such as hotel, travel and trekking agencies in Nepal. The study is based on primary data with 382 responses. The self-administered questionnaires were used to collect the perceptive opinions from the respondents. The study concludes that all age groups and number of years work experience groups of employees’ perception concerning collaboration, trust, learning, centralisation, formalisation, and information technology are similar. Different educational groups of employees have different opinions regarding collaboration, centralisation, and formalisation but their perception is similar to trust, learning and information technology.